Community Resilience of Jeruksawit Village in Facing Covid-19 Pandemic in 2020 (Case Study in Jeruksawit Village, Gondangrejo Subdistrict, Karanganyar Regency) - Rita Mawanti Kusuma Nurbersari; Yasin Yusup; Rita Noviani (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
Coronavirus Disease-2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-COV2). In Indonesia the virus is spreading rapidly from urban to the rural areas. The aim of this study: 1) Determine the distribution moment COVID-19 in the village of Jeruksawit and, 2) Determine the level of resilience of the village community in Jeruksawit terms of health, physical, social, economic, and spatial planning in the face of the COVID-19 pandemic. The used of data source was the result of interviews with officials government and residents of Jeruksawit Village. Observation of village spatial planning as primary data, secondary data from Jeruksawit Village monographs. Data analysis use scoring method based on several indicators using a Likert scale. The results of the research showed that the spread of Covid-19 in Jeruksawit Village was 0 cases. Jeruksawit Village has high resilience to COVID-19 and can doing activities as usual smoothly.